Pengaruh Model Problem Based Learning Berbasis SETS Terhadap HOTS Pada Materi Ekosistem - Aulia Novitasari; Erni Oktavia; Fredy Ganda Putra (Symbiotic: Journal of Biological Education and Science, 2024)
The Higher Order Thinking Skills (HOTS) are crucial in helping students solve problems, including connecting new information with existing knowledge, distinguishing ideas or concepts, reasoning, problem-solving, providing explanations, and hypothesizing. Unfortunately, the HOTS abilities of students are not fully met. A study was conducted to investigate the influence of the Problem-Based Learning model based on SETS on HOTS. This research employed a quasi-experimental design. The population consisted of all tenth-grade science students at MAN 1 Lampung Utara. The samples were taken from X MIA 1 and X MIA 3. Data were collected through HOTS essay tests. Based on the research results, a significance level of sig < 0.05 was obtained, indicating that there is an influence of the Problem-Based Learning model based on SETS on the HOTS of tenth-grade students in the ecosystem material at MAN 1 Lampung Utara